2017
DOI: 10.1002/phar.2038
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Insulin Doses for the Treatment of Hyperkalemia in Patients with Renal Insufficiency

Abstract: In patients with renal insufficiency and hyperkalemia, 5 units of insulin reduced serum potassium to the same extent as 10 units of insulin but with a lower rate of hypoglycemia. Further controlled studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 24 publications
2
46
1
Order By: Relevance
“…The recorded incidence of hypoglycaemia (22%), severe hypoglycaemia (6%) and the median time to detection of hypoglycaemia (108 min) in our study is consistent with previous reports 5 9–13 15–18. The increased prevalence of hypoglycaemia in our sample compared with other cohorts may reflect the exclusion of patients receiving therapies such as dextrose containing intravenous solutions and albuterol that are expected to be protective against the development of hypoglycaemia and were not adequately controlled in previous samples.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The recorded incidence of hypoglycaemia (22%), severe hypoglycaemia (6%) and the median time to detection of hypoglycaemia (108 min) in our study is consistent with previous reports 5 9–13 15–18. The increased prevalence of hypoglycaemia in our sample compared with other cohorts may reflect the exclusion of patients receiving therapies such as dextrose containing intravenous solutions and albuterol that are expected to be protective against the development of hypoglycaemia and were not adequately controlled in previous samples.…”
Section: Discussionsupporting
confidence: 89%
“…Changes in blood glucose remain difficult to predict in patients treated with intravenous insulin and dextrose as no strategy has been conclusively demonstrated to mitigate the risk of subsequent hypoglycaemia. Reduced insulin and/or increased dextrose doses may be associated with a lower incidence of hypoglycaemia while maintaining the potassium-lowering effect but this is not consistent across all studies and hypoglycaemia was still observed in 6.1% to 19.5% of patients 10 12 17 19. Frequent monitoring of blood glucose is an important but underused step toward avoiding the sequelae of hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with studies suggesting that preinsulin blood glucose levels less than 140 mg/dL and the standard 10 units of insulin for hyperkalemia treatment may increase the risk of hypoglycemia. 4,7,9 To decrease the risk of iatrogenic hypoglycemia, we redesigned our hyperkalemia insulin orderset to address the strongest predictors of hypoglycemia (doses of regular insulin greater than 0.14 units/kg and preinsulin blood glucose less than 140 mg/dL). The main changes were weight-based insulin dosing (based on previously published data) 10 and adjustment of glu-cose administration based on the patient's glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Other rapid interventions that can assist in the control of hyperkalemia include insulin administration, 71 particularly in the hyperglycemic patient, and alkali administration if hypobicarbonatemia is present. 72 Sodium-free alkali preparations are under development to avoid the sodium load associated with sodium bicarbonate administration.…”
Section: Recommended Approachesmentioning
confidence: 99%